Twilight of impunity : the war crimes trial of Slobodan Milosevic - Armatta, Judith (e-Duke books scholarly collection., 2010)
This first in-depth treatment of Slobodan Milosevic's trial by an objective, first-hand observer recommends ways to prevent courtroom dominance by a defiant accused while preserving the right to a fair trial.